Sensemaking and sustainability: a sensemaking perspective on the ethical use of big data in marketing strategizing - Wang, Emma (Junhong); Berthon, Pierre; Su, Yiran (Sustainable Development Seen Through the Lenses of Ethnoeconomics and the Circular Economy, 2024)
Despite the ethical concerns over the datafication and surveillance of individuals and groups, companies are making ever greater investments in big data. The assumptions underpinning this movement are: (1) organizations are passive implementers of big data—more data is the inevitable consequence of technology and a competitive necessity for business, (2) more data offers a more objective and accurate picture of reality and (3) more data enables better prediction. We argue that this perspective is strategically unsustainable and abdicates ethical responsibility.
Keywords: Big Data; Organization; Sensemaking; Strategizing; Sustainability; dept.mrk

The impact of generative AI on syllabus design and learning - Kim, Hyoseok; Koo, Thomas K. B. (Journal of Marketing Education, 2024)
This research examines the impact of generative artificial intelligence (AI) on the perception of educational content quality, specifically by comparing AI-generated and human-generated course syllabi in marketing education. Results from four studies indicate a general preference for AI-generated syllabi, attributed to their greater perceived objectivity. This preference is more pronounced in conventional courses but diminishes in unconventional ones, suggesting that the unique aspects of these courses may reduce the advantages of generative AI. In addition, disclosing the AI authorship of syllabi significantly affects their perceived quality negatively, underscoring the impact of transparency on the acceptance of AI-generated educational materials. These findings highlight the potential of generative AI in educational content creation and its limitations in certain contexts. They offer valuable insights for enhancing educational practices and shaping policy decisions to enrich student experiences in the era of AI integration.
Keywords: dept.mrk; peer-reviewed

One of these ads is not like the other: Viewer inability to differentiate issue ads from candidate ads - Forbus, R.; Marchant-Shapiro, T.; Singh, A.S. (International Journal of Interdisciplinary Civic and Political Studies, 2024)
For more than a decade, since the US Supreme Court ruled in Citizen’s United (2010), individuals and groups interested in the outcome of elections have increasingly donated to outside groups that avoid the restrictions imposed on candidates and traditional political action committees (PACs). As a result, total election spending more than doubled in the first five years and has continued to increase since then. Although American political advocacy groups refrain from formal electioneering, much of the increase in spending since Citizen’s United has been directed toward election campaigns under the guise of issue-advocacy ads. This raises the question of whether voters perceive a difference between candidate-sponsored ads and campaign-focused issue-advocacy ads. Unexamined is the impact that advertising by outside groups has on voters and whether voters are even aware of the sponsors of the ads they view. This study addresses whether voters can differentiate between ads sponsored by candidates or outside groups. Using an experimental design, we find that viewers cannot determine the sponsor of campaign ads, despite federal requirements for sponsor disclaimers. © 2024 Common Ground Research Networks. All rights reserved.
Keywords: Ad Differentiation; Ad Sponsorship; Campaign Ads; Issue-Advocacy Ads; Political Ad Disclaimers; Voter Perceptions; dept.mrk; dept.psc; peer-reviewed

A model of academic dishonesty intentions: mediating effects of machiavellianism and differential association - Prince, Melvin; Wang, Emma (Journal of Further and Higher Education, 2024)
Past studies of academic dishonesty typically have been grounded in the theory of planned behaviour. Key predictors of academic dishonesty variables under this framework generally have been attitudes towards academic dishonesty, the impact of peer pressure to engage in such acts, and individual perceptions of related acts. However, planned behaviour theory is silent about the significant impact on academic dishonesty of past academic dishonesty behaviours. The objective of the present study is to analyse, through the lens of social learning theory, the effects of past behaviours that predispose academic dishonesty: differential association, i.e., the effects of individual learning, through interaction with others, of the values, attitudes, techniques, and motives for deviant behaviour, on the prediction of academic dishonesty intentions. Additionally, the study tests the effects of Machiavellianism, or dishonest and deceptive behaviours on the relationship between past academic dishonesty acts and academic dishonesty attitudes. Results of the study reveal that differential association with cheating acceptors strengthens the relationship between academic dishonesty attitudes and intentions. Additionally, Machiavellianism at higher levels intensifies the relationships between past academic dishonesty behaviours and contemporary academic dishonesty attitudes.
_eprint: https://doi.org/10.1080/0309877X.2024.2375307
Keywords: Past cheating behaviour; academic dishonesty; cheating; dept.mrk; differential association; machiavellianism; peer-reviewed; social learning

Exploring the role of the service provider in sharing economy services - Zal, Saeed; Guo, Lin; Tang, Chuanyi; Zhang, Junzhou (Journal of Services Marketing, 2024)
Purpose This paper aims to investigate the role of the service provider in determining customer satisfaction in sharing economy services. The authors sought to examine how the intrinsic and extrinsic cues along with their interactions influence customer satisfaction. Design/methodology/approach This research uses a mixed-methods design to test the hypotheses. Study 1 uses secondary data from Inside Airbnb. Study 2 uses a 2 × 2 × 2 between-subject experimental design. Findings Both studies support the confirmation bias perspective over the expectancy-confirmation perspective in explaining the interplay among different cues in determining customer satisfaction. In the context of Airbnb, in the absence of a Superhost badge, if hosts adopt a reactive communication style, physical presence has a greater impact on customer satisfaction compared to virtual presence. Originality/value This study extends the services marketing literature and cue utilization theory by investigating the dynamic interactions among multiple intrinsic and extrinsic service cues. It shed new light on how a combination of these cues may become additive or redundant in determining customer satisfaction. This study contributes to the services marketing literature by addressing the interactive nature of sharing economy services and the neglected role of service providers.
Keywords: Airbnb; Customer satisfaction; Extrinsic cues; Intrinsic cues; Service provider; Sharing economy; dept.mrk; peer-reviewed